Hubungan Pola Aktivitas Full Day School dengan Sikap Sosial Siswa Kelas XI SMA Islam Terpadu (IT) Ar-Rahman Banjarbaru - Parid Wajdi Al Mujtaba; Ersis Warmansyah Abbas; Dewicca Fatma Nadilla; Heri Susanto (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2024)
Technological developments and advances have had a major influence on the development of morals, morals and ethics. Integrated Islamic schools that implement full day school and boarding school programs are in great demand by parents to shape children's character and avoid the negative impacts of modernization and globalization. Full day school is an education system that implements full day learning. Student activity patterns in Full day school, including academic activities, extracurricular activities and social interactions, have the potential to develop social attitudes. The aim of this research is to analyze the relationship between full day school activity patterns and the social attitudes of students at XI Integrated Islamic High School (IT) Ar-Rahman Banjarbaru. The type of research used is quantitative research with a cross-sectional design. The population of this research is class XI students of SMA IT Ar-Rahman Banjarbaru for the 2023/2024 academic year. The research sample was 32 respondents with a sampling technique using proportional random sampling. The research instrument is a questionnaire and the data analysis technique uses the chi square test. The research results show a p-value of 0.001 (p < 0.05), which means there is a significant relationship between full day school activity patterns and the social attitudes of class XI students at Ar-Rahman Banjarbaru Integrated Islamic High School (IT). The existence of a full day school system can shape students' social attitudes such as honesty, discipline, tolerance, mutual cooperation, politeness, and responsibility.